The Impact of the Non-Implementation of the Optimal Islamic Religious Education Curriculum in Indonesian Schools - Heriyanto; Juliani; Erimawahti; Andini; Hesti Indah Sari (Journal of Contemporary Islamic Primary Education, 2024)
The failure to optimally apply the PAI curriculum has a significant impact on various aspects of education, including students' understanding of religion, character formation, quality of learning, and academic achievement. This research identified several causal factors, such as teacher perceptions, student interests, infrastructure, family environment, government policy, curriculum format, community support, and quality of human resources. The most prominent impacts are students' shallow understanding of religion, difficulty in reading the Koran, and weak internalization of moral values. Apart from that, the non-applicability of the curriculum also contributes to an increase in deviant behaviour, ethical crises, mental health problems, and a decrease in the overall quality of learning. To overcome this problem, comprehensive efforts are needed involving various parties, such as evaluating and revising the curriculum, improving the quality of teachers, providing adequate facilities and infrastructure, collaborating with parents, and effective outreach regarding the importance of religious education.